2016
DOI: 10.1128/jcm.00938-16
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Antifungal Susceptibility Profile of Candida guilliermondii and Candida fermentati from a Multicenter Study in China

Abstract: dWith molecular sequencing as a gold standard, the Vitek MS, Bruker Biotyper MS, and Vitek-2 Compact systems correctly identified 92.7%, 97.0%, and 15.2% of 164 Candida guillermondii isolates, respectively, and none of 8 C. fermentati isolates. All of the isolates showed high susceptibility to echinocandins, but some C. guilliermondii isolates showed low azole susceptibility. Invasive candidiasis (IC) is a public health threat worldwide and is considered a major cause of infection-related morbidity and mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
4
18
2
Order By: Relevance
“…In previous studies, C. guilliermondii sensu stricto and C. fermentati accounted for approximately 90% to 95% and 4.5% to 9% of cases, respectively, with the remaining species of the complex playing a marginal role (less than 1%) (9,14). By contrast, we found a higher frequency of cases caused by C. fermentati (22.7%) and a lower frequency of cases caused by C. guilliermondii sensu stricto (77.2%).…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…In previous studies, C. guilliermondii sensu stricto and C. fermentati accounted for approximately 90% to 95% and 4.5% to 9% of cases, respectively, with the remaining species of the complex playing a marginal role (less than 1%) (9,14). By contrast, we found a higher frequency of cases caused by C. fermentati (22.7%) and a lower frequency of cases caused by C. guilliermondii sensu stricto (77.2%).…”
Section: Discussionsupporting
confidence: 41%
“…The complex exhibited decreased in vitro susceptibility to all of the antifungal agents studied, with rates of resistance to fluconazole and other azoles of approximately 10% to 15% (9,12,14). Up to 10% of the isolates studied here were non-wild type according to the fluconazole ECOFF.…”
Section: Discussionmentioning
confidence: 79%
“…18 Andes et al discussed, with their murine model, that prolonged exposure to azole drugs at non-lethal concentrations may be attributed to the emergence of resistant Candida infections. 19 Compared with the MICs shown previously, 20,21 the strain in the present case seemed to be more resistant to FLCZ and ITCZ, speaking in favor of the possible evolution of azole resistance during the long-term azole exposure before and after engraftment.…”
contrasting
confidence: 66%
“…Andes et al discussed, with their murine model, that prolonged exposure to azole drugs at non‐lethal concentrations may be attributed to the emergence of resistant Candida infections . Compared with the MICs shown previously, the strain in the present case seemed to be more resistant to FLCZ and ITCZ, speaking in favor of the possible evolution of azole resistance during the long‐term azole exposure before and after engraftment. The present case may underline the needs to consider possible azole resistance among HCT recipients, especially those with history of prolonged azole exposure, and the importance of accurate identification of species and prompt examination of the susceptibility in such circumstances.…”
Section: Discussioncontrasting
confidence: 43%
“…Overall, MALDI-TOF MS is an accurate, reliable, and rapid method for the identification of human pathogenic fungi, and new applications for clinically relevant yeasts and filamentous fungi are continuously being developed [43][44][45]. A comparison of two commercially available systems, VITEK MS (bioMérieux) and MALDI Biotyper (Bruker Daltonics) with their associated databases, has shown similar identification efficiencies of clinically relevant yeasts for the two systems [46,47], while other studies found differences between biotyping systems [48,49]. The identification power is improved by including in-house generated reference spectra in the databases [17,43,46] (also see above).…”
Section: Clinical Maldi-tof Ms Applications Benefit Fungal Diagnosis mentioning
confidence: 97%